2022
DOI: 10.1002/ppap.202200128
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid atmospheric pressure plasma generation and DC electrospray aerosolization of plasma‐activated water for surface pathogen disinfection

Abstract: We demonstrate the synergistic effects of combining atmospheric pressure plasma generation together with aerosolization of the resultant plasmaactivated water using direct current electrospraying for effective chemical-free spray-based surface disinfection. Besides facilitating the efficient aerosol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Measured physical properties—(a) density ρ f , (b) viscosity μ f and (c) surface tension σ f —of deionized water (DI) and plasma‐activated water with different electrical conductivities σ e . These trends are consistent with that reported in an earlier study, [ 47 ] at least up to the highest value of σ e = 1 mS/cm measured in that work. The electrical conductivity for the DI water was approximately σ e = 0.003 mS/cm and that for plasma‐activated water was controlled by varying the treatment time, i.e., the exposure duration of DI water to atmospheric pressure plasma.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Measured physical properties—(a) density ρ f , (b) viscosity μ f and (c) surface tension σ f —of deionized water (DI) and plasma‐activated water with different electrical conductivities σ e . These trends are consistent with that reported in an earlier study, [ 47 ] at least up to the highest value of σ e = 1 mS/cm measured in that work. The electrical conductivity for the DI water was approximately σ e = 0.003 mS/cm and that for plasma‐activated water was controlled by varying the treatment time, i.e., the exposure duration of DI water to atmospheric pressure plasma.…”
Section: Resultssupporting
confidence: 94%
“…This enhancement in nebulization rate can be attributed predominantly to the appreciable increase in wettability with the SiO 2 coating-as evidenced by the decrease in the static contact angle, especially at higher values of 𝜎 e (Table 1)-that facilitates the spreading of the liquid over the substrate, leading to longer films and hence a larger (c) surface tension 𝜎 f -of deionized water (DI) and plasma-activated water with different electrical conductivities 𝜎 e . These trends are consistent with that reported in an earlier study, [47] at least up to the highest value of 𝜎 e = 1 mS/cm measured in that work. The electrical conductivity for the DI water was approximately 𝜎 e = 0.003 mS/cm and that for plasma-activated water was controlled by varying the treatment time, i.e., the exposure duration of DI water to atmospheric pressure plasma.…”
Section: Effect Of the Sio 2 Coating On The Nebulization Ratesupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have demonstrated the potential of plasmaactivated aerosols (PAAs) for disinfection (Jiang et al, 2017;Freyssenet and Karlen, 2019;Wong et al, 2020;Chew et al, 2022;Chew et al, 2023). It was observed that most PAA setups utilised commercial aerosol- The change in pH in deionised water samples contained within the first bubbling flask with increasing PAA exposure (A).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the PAW was produced via the corona discharged plasma. From [34]. Copyright 2023 Author(s), licensed under a Creative Commons Attribution (CC BY-NC-ND 4.0) License.…”
Section: Physical Propertiesmentioning
confidence: 99%